Comparing trimodal therapy with radical cystectomy in muscle-invasive bladder cancer: an updated meta-analysis - Al-Qudimat, Ahmad R.; Singh, Kalpana; Ojha, Laxmi K.; Moustafa, Diala Alhaj; Elaarag, Mai; Al-Zoubi, Raed M.; Aboumarzouk, Omar M. (Frontiers in Surgery, 2023)
Background We conducted this meta-analysis to compare the two muscle-invasive bladder cancer (MIBC) treatment modalities in terms of cancer-specific survival (CSS) and other outcome indicators. Method A systematic review and meta-analysis were performed in accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. The search was conducted using various academic databases including Scopus, PubMed, Cochrane database, EMBASE, Chinese biomedical literature database, Wan fang databases, and China National Knowledge Internet databases between 1966 and December 2023. This review protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) No. (CRD42023398977). Result This study included a total of 54,816 patients diagnosed with bladder cancer from 14 studies, of which 6,228 patients were assigned to the trimodal therapy (TMT) group and 48,588 patients were assigned to the radical cystectomy (RC) group. Based on the results, the RC group exhibited a higher rate of survival than the TMT group [pooled hazard ratio (HR) = 1.23, 95% CI: 1.18–1.28, Z = 1.46, P < 0.001]. In terms of CSS, patients in the RC group had a longer CSS compared with those in the TMT group (pooled HR = 1.47, 95% CI: 1.29–1.67, Z = 5.893, P < 0.001). Compared with RC, TMT is significantly associated with an increased risk of both types of mortality (pooled HR: 1.30, P < 0.001). Conclusion Overall, the findings of this meta-analysis suggest that RC treatment may be associated with improved overall survival. Moreover, it was observed that cancer-specific survival was significantly prolonged among patients in the RC group as opposed to those who received TMT. In addition, it was shown that patients who received TMT exhibited a higher risk of all-cause mortality when compared with those who underwent RC.